Advanced multiparametric magnetic resonance imaging of multinodular and vacuolating neuronal tumor. (22nd May 2020) - Lecler, A.; Broquet, V.; Bailleux, J.; Carsin, B.; Adle‐Biassette, H.; Baloglu, S.; Forestier, G.; Bonneville, F.; Calvier, E.; Chauvet, D.; Comby, P. O.; Cottier, J. P.; et al.
Abstract : Background and purpose: Multinodular and vacuolating neuronal tumor (MVNT) of the cerebrum is a rare brain lesion with suggestive imaging features. The aim of our study was to report the largest series of MVNTs so far and to evaluate the utility of advanced multiparametric magnetic resonance (MR) techniques. Methods: This multicenter retrospective study was approved by our institutional research ethics board. From July 2014 to May 2019, two radiologists read in consensus the MR examinations of patients presenting with a lesion suggestive of an MVNT. They analyzed the lesions' MR characteristics on structural images and advanced multiparametric MR imaging. Results: A total of 64 patients (29 women and 35 men, mean age 44.2 ± 15.1 years) from 25 centers were included. Lesions were all hyperintense on fluid‐attenuated inversion recovery and T2‐weighted imaging without post‐contrast enhancement. The median relative apparent diffusion coefficient on diffusion‐weighted imaging was 1.13 [interquartile range (IQR), 0.2]. Perfusion‐weighted imaging showed no increase in perfusion, with a relative cerebral blood volume of 1.02 (IQR, 0.05) and a relative cerebral blood flow of 1.01 (IQR, 0.08). MR spectroscopy showed no abnormal peaks. Median follow‐up was 2 (IQR, 1.2) years, without any changes in size. Conclusions: A comprehensive characterization protocol including advanced multiparametric magnetic resonance imaging sequences showed no imaging patterns suggestive of malignancy in MVNTs. It might be useful to better characterize MVNTs.